2015
DOI: 10.1634/theoncologist.2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Care and Clinical Outcomes of First-Line Trastuzumab-Based Therapy in HER2-Positive Metastatic Breast Cancer Patients Relapsing After (Neo)Adjuvant Trastuzumab: An Italian Multicenter Retrospective Cohort Study

Abstract: Background. We evaluated the patterns of care and clinical outcomes of metastatic breast cancer patientstreated with firstline trastuzumab-based therapy after previous (neo)adjuvant trastuzumab. Materials and Methods. A total of 416 consecutive, HER2-positive metastatic breast cancer patients who had received first-linetrastuzumab-basedtherapywereidentifiedat14Italian centers. A total of 113 patients had presented with de novo stage IV disease and were analyzed separately. Dichotomous clinical outcomes were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
(47 reference statements)
2
18
0
Order By: Relevance
“…For re-treatment with first-line trastuzumab in patients previously treated trastuzumab, two retrospective [17, 18] and one prospective studies [19] have all shown effectiveness. The prospective study with trastuzumab in combination with docetaxel or paclitaxel by Lang et al showed a median PFS of 8.0 months, OS of 25.0 months in 41 patients after a 40-month median follow-up time [19], similar to our results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For re-treatment with first-line trastuzumab in patients previously treated trastuzumab, two retrospective [17, 18] and one prospective studies [19] have all shown effectiveness. The prospective study with trastuzumab in combination with docetaxel or paclitaxel by Lang et al showed a median PFS of 8.0 months, OS of 25.0 months in 41 patients after a 40-month median follow-up time [19], similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…The prospective study with trastuzumab in combination with docetaxel or paclitaxel by Lang et al showed a median PFS of 8.0 months, OS of 25.0 months in 41 patients after a 40-month median follow-up time [19], similar to our results. In the Italian multicenter retrospective cohort study of HER2-positive mBC, trastuzumab re-treatment of patients relapsing from previous (neo)adjuvant trastuzumab therapy showed a PFS of 12.0, ORR of 61.3%, CBR of 72.5%, and OS of 48.2 months [17]. In the retrospective study, trastuzumab as first-line therapy for HER2-positive mBC in patients previously treated with adjuvant trastuzumab showed a two-year OS of 60.0% [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in the TN‐group had either relapsed after stage I–III primary breast cancer or presented with de novo stage IV disease. Because previous studies reported that the presentation with primary metastatic disease does not affect long‐term outcomes, these patients were pooled . The retrospective review of electronic patient records for the purpose of this study was approved by the central ethical review board (METC 15‐046) in addition to the permission of omitting written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…A possible way to study this might be comparing long‐term outcome between patients pretreated with trastuzumab and patients without previous trastuzumab. However, studies investigating this issue have shown conflicting results , possibly due to small numbers of patients , low numbers of events , or short duration of follow‐up . We have therefore performed a retrospective study to compare the efficacy of first‐line HER2‐targeted‐containing chemotherapy between patients who did or did not undergo adjuvant trastuzumab‐based treatment in a large number of patients, determined by a power analysis calculated prior to the start of the study, thereby guaranteeing a sufficient number of events (deaths).…”
Section: Introductionmentioning
confidence: 99%